1977
DOI: 10.1073/pnas.74.10.4365
|View full text |Cite
|
Sign up to set email alerts
|

Transcription termination at the trp operon attenuators of Escherichia coli and Salmonella typhimurium: RNA secondary structure and regulation of termination.

Abstract: Transcription termination at the attenuators of the trp operons of Escherichia coli and Salmonella typhimurium was studied in vitro using DNA restriction fragments as templates. Readthrough transcription beyond the terminators occurred with 5 and 30% efficiency, respectively, in E. coli and S. typhimurium. This difference is correlated with the stability of proposed secondary structures of the respective trp leader transcripts. Secondary structure analyses of the two leader transcripts revealed a well-conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
98
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(104 citation statements)
references
References 28 publications
(24 reference statements)
4
98
1
Order By: Relevance
“…Lee and Yanofsky (1977) concluded that the termination efficiency at the attenuator is correlated with the stability of an embedded secondary structure which is conserved between E. coli and Salmonnella typhimurium; the proposed structures agree with results of a partial RNase T1 digestion that exhibit digestion resistance in the distal portion of this transcript, i.e., where the structural features are located. 32 Thereafter, Oxender et al (1979) conducted structural probing with RNase T1 partial digestion followed by isolation of the comigrating pairing regions in a non-denaturing gel electrophoresis; the base-pairing regions were subsequently identified via denaturing gel electrophoresis and fingerprinting, based on which the two hairpins comprising the terminator structure were drawn. 33 Later on, the secondary structure of DNA template was ruled out as a contributor for this termination signal so the RNA structural features are the one causing the termination.…”
Section: Trp Operon Leadersupporting
confidence: 67%
See 2 more Smart Citations
“…Lee and Yanofsky (1977) concluded that the termination efficiency at the attenuator is correlated with the stability of an embedded secondary structure which is conserved between E. coli and Salmonnella typhimurium; the proposed structures agree with results of a partial RNase T1 digestion that exhibit digestion resistance in the distal portion of this transcript, i.e., where the structural features are located. 32 Thereafter, Oxender et al (1979) conducted structural probing with RNase T1 partial digestion followed by isolation of the comigrating pairing regions in a non-denaturing gel electrophoresis; the base-pairing regions were subsequently identified via denaturing gel electrophoresis and fingerprinting, based on which the two hairpins comprising the terminator structure were drawn. 33 Later on, the secondary structure of DNA template was ruled out as a contributor for this termination signal so the RNA structural features are the one causing the termination.…”
Section: Trp Operon Leadersupporting
confidence: 67%
“…9,38,39 Indeed, the functional importance of the second hairpin for the transcriptional termination is illustrated by the reduced transcription termination frequency observed in experiments destabilising the central GCC pairing of this hairpin, such as by in vivo mutational analysis or in vitro substitution of G-C bond by I-C bond. 32,[40][41][42] Moreover, mutational analysis progressively disrupting the first hairpin still preserves the production of the attenuated transcript, suggesting that the second hairpin itself is sufficient for the termination. 9,42 Anti-terminator structure Anti-terminator structure disrupts the two terminator hairpins…”
Section: Trp Operon Leadermentioning
confidence: 99%
See 1 more Smart Citation
“…1) (4,32,38). In principle, the attenuation mechanism controlling the ilv operon appears to be quite similar to that found to control operons involved in tryptophan (35), leucine (19), phenylalanine (61), histidine (3), and threonine (17) biosynthesis: the leader region specifies a short peptide containing a disproportionate frequency of the amino acids that are found to regulate the operon. Thus, the rate at which the leader can be translated serves to sense whether the regulatory amino acid is in short or ample supply.…”
mentioning
confidence: 83%
“…. C'B'A' have been described in the leader sequences in both prokaryotes (Lee & Yanofsky, 1977) and animal viruses (Chow et al, 1977), at the ends of insertion elements (Ohtsubo & Ohtsubo, 1978) andin several transposable DNA segments carrying antibiotic resistance genes (Kleckner et al, 1975;Heffron et al, 1975). It is possible that many modes of recombination occur through self-complementary sequences or that they are involved in the regulation of transcription.…”
Section: Discussionmentioning
confidence: 99%